Ultra-Wideband Vertically Polarized Omnidirectional Antenna With Dual Metal Loops - Peng, Jian Dong; Fu, Dong Qiang; Ye, Liang Hua; Shi, Xinrong (Frontiers in Physics, 2022)
An ultra-wideband vertically polarized monopole antenna having excellent omnidirectional radiation pattern is proposed. It consists of a four-sector monopole, dual metal loops and a metal reflector. The four-sector monopole is employed as radiator and excited by a 50 Ω coaxial cable to realize vertical-polarized omnidirectional radiation pattern and good impedance matching. Then two metal loops surrounding the monopole are used to further enhance the impedance matching and improve the gain variation. The antenna has an ultrawide bandwidth of 103% (1.63–5.1 GHz) for return loss > 15 dB. It also obtains a steady gain of 3.25 ± 1.35 dBi and a very small gain variation of less than 0.9 dBi within the ultrawide band. These performances indicate that the proposed antenna is competitive for 2G/3G/4G/5G indoor mobile communications.